The Role of Firm Size, Leverage, and Governance in Earnings Management: A Comparative Study of IDX and BRVM - Cisse, Mohamed; Priantinah, Denies (Nominal: Barometer Riset Akuntansi dan Manajemen, 2025)
This research aimed to comparatively analyze the influence of key corporate governance mechanisms on earnings management in the consumer goods industry across two distinct markets: the Bourse Régionale des Valeurs Mobilières (BRVM) and the Indonesia Stock Exchange (IDX) during the 2019-2022 period. The study employed simple linear regression to analyze the data. The results indicate a notable divergence in the impact of these governance variables between the two exchanges. For IDX-listed companies, a statistically significant relationship was observed exclusively between leverage and earnings management. The remaining variables, company size, independent board of commissioners, audit quality, and managerial ownership, did not exhibit a significant influence. Conversely, the analysis of BRVM-listed firms showed that company size and managerial ownership were significant predictors of earnings management, whereas leverage, the independent board of commissioners, and audit quality were not. Keywords: Earnings Management, Company Size, Leverage, Corporate Governance Mechanisms ABSTRAK Penelitian ini bertujuan membandingkan dampak mekanisme tata kelola, termasuk Ukuran Perusahaan, Leverage, Dewan Komisaris Independen, Kualitas Audit, dan Kepemilikan Manajemen, terhadap Manajemen Laba di Industri Barang Konsumen yang terdaftar di BRVM dan IDX dari tahun 2019-2022. Analisis regresi linear sederhana digunakan sebagai Teknik analisis data penelitian ini. Hasil penelitian menunjukkan perbedaan yang signifikan antara BRVM dan IDX terkait pengaruh mekanisme tata kelola korporat terhadap Manajemen Laba. Di IDX, Leverage secara signifikan mempengaruhi Manajemen Laba. Selanjutnya, Ukuran Perusahaan, Dewan Komisaris Independen, Kualitas Audit, dan Kepemilikan Manajerial tidak signifikan. Selanjutnya, pada perusahaan yang terdaftar pada BRVM , Ukuran Perusahaan dan Kepemilikan Manajerial secara individual menunjukkan pengaruh signifikan terhadap Manajemen Laba. Namun, Leverage, Dewan Komisaris Independen, dan Kualitas Audit tidak menunjukkan pengaruh signifikan terhadap Manajemen Laba. Kata Kunci: Manajemen Laba, Ukuran Perusahaan, Leverage, Mekanisme Tata Kelola Perusahaan